If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5z + -8)(4 + z) = 0 Reorder the terms: (-8 + 5z)(4 + z) = 0 Multiply (-8 + 5z) * (4 + z) (-8(4 + z) + 5z * (4 + z)) = 0 ((4 * -8 + z * -8) + 5z * (4 + z)) = 0 ((-32 + -8z) + 5z * (4 + z)) = 0 (-32 + -8z + (4 * 5z + z * 5z)) = 0 (-32 + -8z + (20z + 5z2)) = 0 Combine like terms: -8z + 20z = 12z (-32 + 12z + 5z2) = 0 Solving -32 + 12z + 5z2 = 0 Solving for variable 'z'. Factor a trinomial. (-4 + -1z)(8 + -5z) = 0Subproblem 1
Set the factor '(-4 + -1z)' equal to zero and attempt to solve: Simplifying -4 + -1z = 0 Solving -4 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1z = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1z = 0 + 4 -1z = 0 + 4 Combine like terms: 0 + 4 = 4 -1z = 4 Divide each side by '-1'. z = -4 Simplifying z = -4Subproblem 2
Set the factor '(8 + -5z)' equal to zero and attempt to solve: Simplifying 8 + -5z = 0 Solving 8 + -5z = 0 Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -5z = 0 + -8 -5z = 0 + -8 Combine like terms: 0 + -8 = -8 -5z = -8 Divide each side by '-5'. z = 1.6 Simplifying z = 1.6Solution
z = {-4, 1.6}
| (x+4)x=480 | | 9x^2-36x-27=18 | | 12x^2+24x+24=48 | | s(t)=-16t^2+128t+5 | | x^2-12x+10=-1 | | -7u^2+30u-8=0 | | x^2+10x-7=4 | | 28-x/5=7/10 | | -5/2w-2/3=7/6w-2 | | 144=4t | | W+2w=6-6 | | V^2+16v+57=-7 | | 1/5y-7=-3/5y-7/3 | | N^2+5n-8=6 | | (x+5)(x+5)+(y-3)(y-3)=25 | | 5n/2-5/7=95/14 | | 1/5y-7=-3/5-7/3 | | 7-wx=vx+3 | | 2/3-5/2y=-2/7 | | 5x/8-3=22 | | -3/2=-5/2x-7/3 | | 4/7y-3/2=-7/5 | | 5x+(x-8.4)=249.38 | | 8x^2=5(x-2) | | 5/3-9/4y=-1/2 | | 3w+10=6w-11 | | (200x-5000)/200x=.3 | | Ln(x+1)-2Ln(x)=0 | | 60=17+d | | log(x+2)=-log(12) | | f(x)=3sinx+4 | | 65-.2=35 |